Anatomy of Orion Molecular Clouds—The Astrochemistry Perspective/Approach - Sahu, Dipen; Liu, Sheng-Yuan; Liu, Tie (Frontiers in Astronomy and Space Sciences, 2021)
The Orion molecular cloud (OMC) complex is the nearest and perhaps the best-studied giant molecular cloud complex within which low-mass and massive star formation occur. A variety of molecular species, from diatomic molecules to complex organic molecules (COMs), have been observed in the OMC regions. Different chemical species are found at different scales—from giant molecular clouds at parsec scales to cloud cores around young stellar objects at hundreds of au scales, and they act as tracers of different physical and chemical conditions of the sources. The OMC, therefore, is an ideal laboratory for studying astrochemistry over a broad spectrum of molecular cloud structures and masses. In this review, we discuss the usage of astrochemistry/molecular tracers and (sub) millimeter observations to understand the physical and chemical conditions of large-scale molecular clouds, filaments, and clumps down to cores and protostars in the OMC complex as a demonstration case.